2007
DOI: 10.1002/ps.1501
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate‐resistant crops: adoption, use and future considerations

Abstract: GRCs represent one of the more rapidly adopted weed management technologies in recent history. Current use patterns would indicate that GRCs will likely continue to be a popular weed management choice that may also include the use of other herbicides to complement glyphosate. Stacking with other biotechnology traits will also give farmers the benefits and convenience of multiple pest control and quality trait technologies within a single seed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
197
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(205 citation statements)
references
References 5 publications
1
197
0
7
Order By: Relevance
“…It has been used extensively in conjunction with genetically modified crops since 1996 [14,15]. It is estimated that 91% of the soybeans, 22% of the corn, and 23% of the cotton crop hectares in the United States were planted as herbicide-tolerant varieties in 2009 ( [16]; http://www.ers.usda.gov/Data/BiotechCrops/).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used extensively in conjunction with genetically modified crops since 1996 [14,15]. It is estimated that 91% of the soybeans, 22% of the corn, and 23% of the cotton crop hectares in the United States were planted as herbicide-tolerant varieties in 2009 ( [16]; http://www.ers.usda.gov/Data/BiotechCrops/).…”
Section: Introductionmentioning
confidence: 99%
“…In one study, it was reported that air concentrations of glyphosate were below 15.7 mg/m 3 during silvicultural spraying periods [29]. Thus, the occurrence and behavior of atmospheric glyphosate are still largely unknown even though glyphosate is the most widely used herbicide in the world [15,30].…”
Section: Introductionmentioning
confidence: 99%
“…Since 1996, because of a very high level of adoption of genetically modified glyphosate-resistant crops (that is, 80 million Ha in 2006 in Argentina, Brazil, Canada and USA), glyphosate has been intensively used across important agricultural regions (reviewed by Dill et al, 2008). In a relatively short period of time, large-scale usage of glyphosate as a principal tool for weed control in glyphosate-resistant crops without diversity has resulted in glyphosate-resistant weeds and shifts in weed communities (reviewed in Owen, 2008;Powles, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term differences have had an affirmative environmental issue by diminishing soil erosion [21], fueling the needs for soil cultivation [22], and numbering herbicides with groundwater advisories [23], leading to a slight reduction in the overall environmental impact quotient of herbicide use [24,25]. Because of the adoption of herbicide-resistant crops, conservation tillage used in crop production has increased [18,26,27], and the volume of herbicides used in HRCs has decreased [28]. Finally, the effect on soil and plant microbial populations has not been shown to be a potential environmental risk [29,30].…”
Section: Zvonko Pacanoskimentioning
confidence: 99%